2016
DOI: 10.4028/www.scientific.net/msf.840.427
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Fabricated Light Foamed Concrete in Reducing Radon from Building Material

Abstract: Three of Light Foamed Concrete (LFC) have been obtain by using different formula of Cement:Aggregates. The brick was locate into a closed Perspex box and the net of 222Rn concentration level have been measured for 5 consecutive days. The results show the LFC 3 has produced the lowest of net 222Rn concentration level in air, followed by LFC 2 and LFC 1, respectively. The result also show the 222Rn concentration level have been influenced by the temperature and relative humidity in air.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Hence, each average of 222 Rn reading for raw materials were deducted to the background reading (0.977 pCi/L) to obtain the nett 222 Rn concentrations by using the formula in Eq. 1 [2,8]. Thus, nett of 222 Rn concentration from raw red brick was revealed at -0.22 pCi/L.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Hence, each average of 222 Rn reading for raw materials were deducted to the background reading (0.977 pCi/L) to obtain the nett 222 Rn concentrations by using the formula in Eq. 1 [2,8]. Thus, nett of 222 Rn concentration from raw red brick was revealed at -0.22 pCi/L.…”
Section: Resultsmentioning
confidence: 95%
“…It is a form of radioactive gas and one of the contributors for lung cancer besides smoking due to the emission of alpha particles [1]. 222 Rn concentration released from brick was originated from its aggregates which are sand, cement and clay [2].…”
Section: Introductionmentioning
confidence: 99%
“…The maximum average value of radon concentration was observed 14.7 Bq/l in well water used for drinking and irrigation while minimum was found 5.37 Bq/l in tap water used for drinking. Saidi et al (2016) studied the radon concentration in three light foamed concrete which were produced by using different cement to aggregate ratios to find the factor that influence the production of radon from fabricated building materials (Saidi et al, 2016). The results revealed that LFC 3 has produced lowest radon concentration in air, followed by LFC 2 and LFC 1, respectively.…”
Section: Summary Of the Resultsmentioning
confidence: 99%
“…Radon (222Rn) is one of the radioactive gases that contributes towards background radiations [1][2]. It is occurred naturally in the environment from the Uranium-238 decay series in the soil that originate from the Earth's crust.…”
Section: Introductionmentioning
confidence: 99%
“…Emanation of radon towards surrounding poses high risk for health due to the successively decay of their daughters of alpha (α) particles [1]. The inhalation of the gas and its decay products into the respiratory system will be absorbed by the lung tissues and unfortunately increases the risk of lung cancer and other health problems [2,[4][5][6][7].Theoretically, the 222 Rn concentrations might be influenced by its location, based on the activity that has been conducted such as mining industry and radiations work. Human-made of radioactive chemicals have enter the environment from activities such as mining and the use of radioactive materials in nuclear medicine, military, industrial applications, consumer products and nuclear power generation.…”
Section: Introductionmentioning
confidence: 99%